The insider (The Insider, 1991)
Bulgarian digest monthly.Published by The Insider Agency Ltd., a joint venture of ELTEX Ltd. and the Open Society Fund - Sofia.With special issue in Jan. 1998: "The re-birth of Bulgaria, 1996/1997".Has supplement: Business & current affairs.